1994
DOI: 10.1037/0022-0167.41.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Multicultural Counseling Inventory: A self-report measure of multicultural competencies.

Abstract: This article presents the Multicultural Counseling Inventory (MCI), a self-report instrument that measures multicultural counseling competencies. Study 1 comprised 604 psychology students, psychologists, and counselors in a midwestern state. In Study 2, respondents were a national random sample of 320 university counselors. Instrument analysis included exploratory principalaxis factor analysis with oblique rotation, assessment of factor congruence between the factor structures of the 2 samples, LISREL confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
385
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(403 citation statements)
references
References 49 publications
16
385
0
2
Order By: Relevance
“…The content validity of the MCI was established by raters' classification of items into correct subscale categories and expert evaluation of item clarity. Both exploratory and confirmatory factor analyses provided evidence supporting the oblique four-factor model underlying the MCI (Sodowsky et al, 1994;Sodowsky, 1996). To evaluate the use of the MCI in multicultural counseling training, the full scale and subscale posttest scores were found to be significantly higher than pretest scores after a multicultural counseling course.…”
Section: Criterion Measures Multicultural Counseling Inventory (Mci)mentioning
confidence: 81%
See 3 more Smart Citations
“…The content validity of the MCI was established by raters' classification of items into correct subscale categories and expert evaluation of item clarity. Both exploratory and confirmatory factor analyses provided evidence supporting the oblique four-factor model underlying the MCI (Sodowsky et al, 1994;Sodowsky, 1996). To evaluate the use of the MCI in multicultural counseling training, the full scale and subscale posttest scores were found to be significantly higher than pretest scores after a multicultural counseling course.…”
Section: Criterion Measures Multicultural Counseling Inventory (Mci)mentioning
confidence: 81%
“…Bandura (1997) (Constantine & Ladany, 2001;Sue, 2001;Sue et al, 1982;Sue et al, 1992); (b) models of multicultural counseling (D'Andrea & Daniels, 2001;Fuertes & Gretchen, 2001;Ponterotto et al, 2000); (c) assessment of multicultural counseling competence (Coleman, 1996;D'Andrea et al, 1991;LaFromboise et al, 1991;Ponterotto et al, 2002;Sodowsky et al, 1994;Worthington, Mobley, Franks, & Tan, 2000); and (d) training of multicultural competencies (Abreu et al, 2000;Constantine, 2001a;Constantine & Ladany, 2000;Constantine, Ladany, Inman, & Ponterotto, 1996;Ponterotto & Casas, 1987;Quintana & Bernal, 1995). In addition to the progress made in theory and assessment, a recent survey indicated that 73% of APA-accredited counseling psychology programs offered one or more multicultural courses, and 42% of them required a multicultural course (Quintana & Bernal, 1995).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the knowledge subscale of the MCI has been used in studies examining the impact of training on multicultural counseling competencies of school psychologists and clinical students (e.g., Castillo, 2007;Williams, 2005). This scale assesses a counselor's breadth and grasp of the knowledge base of multicultural counseling research, cultural information, and treatment strategies (Sodowsky, Taffe, Gutkin, & Wise, 1994). Another measure that has been frequently used to measure participants' learning is the Multicultural Awareness Questionnaire (Law, 1998).…”
Section: Diversity Training Outcomesmentioning
confidence: 99%